A Comparison of Geologic Structure Detection of Sumatera Island Using Goce Satellite Gravity Data and Sgg-Ugm-2 Data - Al Shida Natul; Leni Sophia Heliani (UIR PRESS, 2022)
GOCE gravity satellite data can be used for regional fault detection because the observation area is wide and not limited by area. In this study, GOCE satellite data is used to detect geological structures on the island of Sumatra, the results of which are used as the basis for disaster mitigation. GOCE data and SGG-UGM-2 were processed using the GOCE User Toolbox (GUT) software to produce a gravity disturbance map and a complete bouguer anomaly map. The GOCE obtained results were validated using the SGG-UGM-2 high-resolution gravity model data. The calculation results obtained that the gravity disturbance value from the GOCE data was around -140 to 200 mGal, while the value of the gravity disturbance from the SGG-UGM-2 data was around -180-300 mGal. The GOCE gravity disturbance map and the SGG-UGM-2 can detect the Subduction Trench, Mentawai Fault, and West Andaman Fault on Sumatra Island with negative values, while the Sumatran Fault Zone (SFZ) along Sumatra Island with positive values ​​in line with the presence of mountain ranges. The results of the SGG-UGM-2 data processing for the gravity disturbance are more detailed than GOCE because the SGG-UGM-2 data degree is higher than that of GOCE. GOCE complete bouguer anomaly value is around 40-560 mGal, while the value of complete bouguer anomaly SGG-UGM-2 is around 60-560 mGal. The complete bouguer anomaly maps from GOCE and SGG-UGM-2 can detect patterns from the Subduction Trench, Mentawai Fault, and West Andaman Fault but cannot clearly detect SFZ. The complete bouguer anomaly can also detect differences between oceanic and continental crust. The GOCE and the SGG-UGM-2 complete bouguer anomaly map show almost similar patterns and the ability to detect geological structures for sub and regional Sumatra Island. In addition, GOCE data detect geological structures more clearly than GRACE data.